Tax Avoidance: Critical Analysis of Current Regulations and Proposals for a Future Reform - Echaiz Moreno, Daniel (2014)
This paper describes and analyzes the configuration, the normative regulation and assumptions of tax avoidance and its differentiation from tax evasion, current regulations on matters related to tax avoidance, disputes relating to this figure due supported, the impact of international tax avoidance through tax havens figure, the way our country aims to combat this figure and finally propose suggestions for improving the anti-elusive regulations in order not to infringe against the taxpayer and any proper legal regulation.